Content Analysis of Image Restoration Theory in the Film Sully 2016 - Ramadhani, Marsha; Oktaviani, Rani Chandra (Communicare : Journal of Communication Studies, 2023)
Aside from entertainment, a film can also be considered a form of communication. Films based on true stories have gained popularity among the general public due to their curiosity about what actually happened. Viewers of true-story films want to see how the main character solves the problems or crisis portrayed in the film and find inspiration and motivation for their own lives. This research aims to examine the content of Image Restoration Theory in the film Sully. This study employs a qualitative descriptive method, utilizing data collection techniques involving document analysis and literature review. The findings of this research reveal that in the film Sully have several Image Repair Strategies content that employed by the main character, Sully, in the post-Hudson River incident moments. There are 1 Reduction of Offensiveness strategy, 3 Denial strategies, and 1 Corrective Action strategy within the Image Repair Strategies component. It was also found that Sully did not employ Evasion of Responsibility and Mortification strategies, indicating his confidence that he did not commit the alleged mistakes.